Hybridge: Bridging Spatiality for Inclusive and Equitable Hybrid Meetings - Panda, Payod; Tankelevitch, Lev; Spittle, Becky; Inkpen, Kori; Tang, John; Junuzovic, Sasa; Qi, Qianqian; Sweeney, Pat; Wilson, Andrew D.; Buxton, Bill; Sellen, Abigail; Rintel, Sean (CSCW 2024, 2024)
Hybrid meetings limit inclusion for remote participants. The Hybridge experimental system provides different interfaces for remote and room endpoints, focusing on improving inclusion via shared spatiality and remote agency. In-room participants see remotes on displays around a table, and remotes see video integrated into a digital twin. Remotes can choose where to appear and from where they view the room. We tested Hybridge in a within-subjects study of group survival tasks. An in-person condition was followed by a counterbalanced order of hybrid traditional videoconferencing ("Gallery") and Hybridge. We found that co-presence and agency differences between in-room and remotes were alleviated in Hybridge but remained in Gallery. Physical presence for remotes was higher in Hybridge than Gallery. Conversation flow was better in Hybridge than Gallery, but ease of awareness was not different. We argue that asymmetry should be embraced when designing hybrid meeting systems, with inclusivity achieved by tailoring features for the needs of different endpoints.